(untitled) (International Journal of Communication Systems and Network Technologies, 2023)
The two synonymous terms: Text Mining (TM) and Information Extraction (IE) are very closely knit. Text Mining is all about tracing patterns in the natural language text where as Information Extraction is extraction of a specific information in the unstructured data. IE modules have off late been automated using the Machine Learning approach. Here the system integrates the TM and IE process in the light of Machine Learning to make a better knowledge extraction system for information interpretation and representation of unstructured data module NLIIRS. This paper presents a framework by the application of a machine learned information extraction system on text to trace interesting relations. The rules mined while developing a database from the text can be used in future documents for efficient information extraction as the recall value improves.